A Study of the Mechanism of Government Intervention on Excess Capacity Through the Enterprise Overinvestment in China. (May 2020) - Hu, Biliang; Liu, Zhiyi; Fan, Sha
This article summarizes government publications focusing on excess capacity from the 1990s to 2016 and argues that the market-oriented principle needs to be established to deal with the long-standing excess capacity issues in China. Based on the specificity of the long-term excess capacity in China, this article puts forward the hypothesis: The excess capacity in China is derived from the enterprise's overinvestment, and the government intervention is one of the main drivers of the problem. The intervention is actuated by the GDP-based government performance assessment through such means as offering privileges on land use, environmental ignorance, natural resource provision and financial support. This article (a) calculates capacity utilization of 30 manufacturing industries, (b) builds a 'mediation effect model of overinvestment', and (c) makes use of the industrial data, economic development data and capacity utilization from 1998 to 2017 to test the hypothesis. The result shows that government intervention indeed has a significant influence on excess capacity. The support for land use and the tolerance for environmental pollution are two of the most persuasive reasons. Therefore, the Chinese government needs to make greater efforts to deepen the market reforms, standardize and improve the factor market so as to accelerate innovation, and push for industrial upgrading.